Soft X-ray photoelectron spectroscopy study on the P segregation process and its effect on the electronic structure of Fe2P(0001). (13th June 2019) - Sugizaki, Yuichi; Shimato, Yuki; Yoshida, Tomoya; Sugimoto, Riki; Maejima, Naoyuki; Edamoto, Kazuyuki
Abstract: The change in the amount of P atoms in the surface region of Fe2 P(0001) as a function of annealing temperature and its effect on the surface electronic structure have been studied by Auger electron spectroscopy (AES) and soft X-ray photoelectron spectroscopy (PES). The AES study showed that the amount of surface P atoms was reduced by Ar + ion sputtering (2 kV, 10 min). When the surface was subsequently annealed, the amount of surface P atoms was further reduced with increasing annealing temperatures up to 400 °C, while it was increased by annealing at temperatures higher than 400 °C. It was deduced from the analyzes of P 2p core-level PES spectra that two processes proceeded when the Ar + ion sputtered Fe2 P(0001) was subsequently annealed; one is the desorption of P atoms weakly bonded to the surface and the other is the segregation of P atoms from the bulk toward the surface. The AES results can be explained by the fact that the former and latter processes were dominant when the sputtered surface was annealed at <400 °C and at >400 °C, respectively. The valence band PES study showed that the 3d states of surface Fe atoms were not effectively stabilized by bonding with surrounding P atoms even when the segregation of P atoms toward the surface proceeded, unlike the situation of Ni2 P(0001).